Randomly primed PCR amplification of pooled DNA reveals polymorphism in a ruminant repetitive DNA sequence which differentiates Bos indicus and Bos taurus - Kemp, Stephen J.; Teale, A.J. (Wiley, 1994)
By amplification of pools of DNA representative of different bovine populations with single short oligonucleotide primers of random sequence, we were able rapidly to identify markers which distinguish the two major subspecies of domestic cattle, Bos taurus and B. indicus. One of the marker polymorphisms was found to be in a novel, dispersed DNA sequence which occurs in several ruminant species. The marker will assist in the detection of crossbreeding between Zebu and B. taurus types where this threatens a potentially valuable trypanosomiasis‐resistant B. taurus genetic resource in West Africa. In addition, the marker will be useful for exploration of the evolutionary relationships of the major subspecies of domestic cattle. The general approach used to identify population‐specific DNA polymorphisms has potentially broad application in definition of species, breeds and populations and will be of generic value in studies of genome evolution.